Impact of New Year's Eve fireworks on the size resolved element distributions in airborne particles - Stefan Tanda; Roman Ličbinský; Jitka Hegrová; Walter Goessler (Environment International, 2019)
New Year's Eve fireworks represent one of the most unusual atmospheric pollution events in the course of a year. A majority of particles aerosolized by burning of fireworks consist of metals and their compounds used in firework displays. In this study, ambient particulate matter was sampled using a 14 stage cascade impactor in two European cities during turn of the years 2016/17 and 2017/18. Concentrations of 33 elements were determined by inductively coupled plasma mass spectrometry. To assess the impact of New Year's Eve fireworks on ambient air quality, chemically resolved size distributions of particles with diameters between 15 nm and 10 μm collected during fireworks episodes were compared to ones collected in normal winter weeks. For some metals a distinct shift of their concentration maximum related to fireworks could be observed, which is in between the maxima for accumulation and coarse mode particles. Concentrations of these elements (Sr, Ba, Mg, Bi, Al, Cu and K) were also higher during weeks with fireworks episodes than during control weeks. Although New Year's Eve fireworks only take place once a year, these results show that air pollution caused by fireworks can be a potential health risk, especially for people with pre-existing diseases. Keywords: Particulate matter, ICPMS, Element distribution, Airborne particles, New Year's Eve fireworks